OPTIMIZING PEDAGOGICAL STRATEGIES AND CURRICULA IN PREPARATION FOR THE AT-TANAL AL-ARABI CERTIFICATE: DEVELOPING AND ASSESSING INTEGRATED SKILLS - Zamira Z. Tojiyeva (International Journal of Literature and Language Studies, 2026)
This article critically examines the pedagogical strategies and curricular frameworks employed in preparing learners for the At-Tanal al-Arabi (Arabic Attainment) certificate examination. Drawing on theoretical contributions from international and national scholars in applied linguistics, language assessment, and educational methodology, the study analyzes the extent to which current instructional approaches develop integrated language skills — reading, listening, writing, speaking, and mediation — in a coherent and contextually authentic manner. The article argues that conventional skill-segregated curricula are insufficient for meeting the integrated competency standards of the At-Tanal examination and proposes a task-based, content-driven pedagogical model grounded in formative assessment. The study further engages with debates surrounding communicative competence, intercultural awareness, and digital supplementation in Arabic-as-a-Foreign-Language (AFL) instruction within Uzbek and broader Central Asian educational contexts.